Kecerdasan Emosional Memoderasi Pengaruh Tekanan Anggaran Waktu dan Tekanan Ketaatan pada Auditor Judgement BPK Pusat - Wijaksana, Prema Laksmi; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p05, 2019)
This study aims to determine the moderating ability of emotional intelligence to time budget pressure and compliance pressure to the auditor. The population in this study was the entire auditor auditor IIIA at the Central BPK office. The number of samples used in this study were 68 respondents from 68 auditor auditor IIIA at the Central BPK office. The size of the sample is based on the technique of determining saturated samples. Data collection in this study was conducted by questionnaire method. The data analysis technique used is the analysis of Moderated Regression Analysis (MRA). The results showed that time budget pressure and compliance pressure negatively affected auditor auditor auditor IIIA Central BPK and emotional intelligence were able to moderate the influence of time budget pressure and auditor compliance judgment auditor auditorat pressure IIIA Central CPC. Keywords : Time budget pressure, Compliance pressure, emotional intelligence, Auditor judgment.